Класифікація операторів однієї дискретної антисипаційної системи першого порядку - Lazarenko, S. V.; Makarenko, O. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2013)
Modeling of the computing systems with anticipation belongs to modern direction of mathematical modeling of the variety of social-economical and ecological processes. By using them it is convenient to formalize such models as population interactions, conflicts over scarce resources, crowd movement and so on. In this modeling field, ones focused lately on the construction and investigation of new anticipatory models for the artificial neuron networks, cellular automata etc. Paper is devoted to classification of the operators of discrete quadratic strong anticipatory system with first order anticipation in the control parameter space. We get the sufficient condition for an appearance of the attractor with a self-similar structure of such kind which can be considered as fractals. During investigation we use Lamerey's diagrams and developed multithreads software. Significant applied interest performs the getting of the dependences between fractal dimensions of the attractors and control parameters.